Effects of Technology Transfer Policies on the Technical Efficiency of Korean University TTOs - Jaepil Han (KDI Journal of Economic Policy, 2018)
The Korean government has provided various policy devices to boost technology transfers between academia and industry since the establishment of the Technology Transfer Promotion Act in 2000. Along with the enactment of the law, the Korean government mandated the establishment of a technology transfer office at national and public universities and encouraged technology transfer activities. Despite the quantitative expansion of technology transfer offices (TTOs), operational inefficiency was brought up. As a supplementary policy, the Korean government implemented a line of projects to support the labor and business expenses of leading TTOs. This research questions whether the project greatly affected the technical efficiency of TTOs. We analyze publicly available university panel data from 2007 to 2015 using a one-step stochastic frontier analysis. The results suggest that the program was marginally effective at shifting the technical efficiency distribution to the right on average, but it failed to maximize its impact by diversifying the policy means based on targets. The marginal effects of the program on technical efficiency differ according to the research capability and size of each school. We also compare technical efficiency against the licensing income at the start and end of the program. Technical efficiency increased for the leading TTOs, and both measures show improvements for unsupported TTOs. Our empirical results imply that diversifying the program for universities with different characteristics may have improved the effectiveness of the policy.
Keywords: L24; O32; O38; I28; 330; Technology Transfer; Technology Transfer Office; Efficiency; Stochastic Frontier Analysis